PENGARUH KUALITAS PENGANGGARAN DAN KOMPETENSI SUMBER DAYA MANUSIA BIDANG KEUANGAN TERHADAP KINERJA KEUANGAN SEKOLAH - Ahmad Yusron; Ngurah Ayu Nyoman Murniati; Muhammad Prayito (Jurnal Manajemen Pendidikan (JMP), 2023)
ABSTRACT             Schools have the duty to manage finances based on the applicable financial management principles. School financial management in SMK throughout Batang Regency has not fully implemented the principles of accountability and efficiency even though the existing budget is received from various sources and issued to several posts. Vocational High School Education Institutions have an obligation to report their activities to the public or related parties. Accountability and reporting of funds raised is a manifestation of accountability.            This study aims to 1) determine the effect of budgeting quality on school financial performance; 2) analyze the effect of budgeting quality on school financial performance; 3) analyze the competence of financial human resources on the school's financial performance and 4) analyze the effect of the quality of budgeting and human resource competence on finance together on the school's financial performance.This research is an explanatory research with a quantitative approach. The study population consisted of 86 teachers at SMK in Batang Regency. The research sample was 86 people with total sampling technique. The research instrument used a questionnaire. Data analysis used descriptive and multiple linear regression.            The descriptive data shows that 1) the quality of budgeting is in the fairly good category with a mean value of 114.22; 2) the competence of human resources in the field of finance is in the fairly good category with a mean value of 114.21 and 3) the school's financial performance is in the good category with a mean value of 125.06. The results of the hypothesis test show that 1) there is an effect of the quality of budgeting on the financial performance of the schools studied. state with the equation Ῡ=80.444+0.378X₂, a correlation strength of 0.366 with a contribution of 0.134 or 13.4%; 3) there is an effect of human resource competence in the field of finance on school financial performance which is expressed by the equation Ῡ= 48.313+0.659X₃, a correlation strength of 0.622 with a contribution of 0.387 or 38.7%.There is a positive influence on the quality of budgeting and the competence of human resources in the field of finance which jointly affect the financial performance of schools which is expressed by the equation Ῡ= 36.175 + 0.109Xₗ + 0.158X₂ + 0.415 X₃, output correlation 0.649 with a contribution of 0.400 or 40% Keywords: Quality of budgeting, competency of financial human resources, and                      school's financial performance.